1996
DOI: 10.3354/meps135021
|View full text |Cite
|
Sign up to set email alerts
|

Year-class strength and growth rate in young Atlantic cod Gadus morhua

Abstract: ABSTKACT. The paradigm relat~ng early life history growth rate to survival rate and/or year-class strength has remained largely untested among marine fishes. Using Atlantic cod Gadus morhua on Georges Bank (NW Atlantic) as a test species, I reconstructed the larval and juvenile g]-owth sequences of 5 successive year-classes of cod and related them to 2 independent indices of year-class strength. Larval and juvenile growth sequences reconstructed from the otolith microstructure of young-of-theyear juveniles dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
137
1
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(148 citation statements)
references
References 0 publications
7
137
1
3
Order By: Relevance
“…Rather, early growth per se simply had much more important effects on mortality than later growth, effects that were preserved till settlement and extended into recruitment. This situation contrasts with that in temperate species such as cod, where recruitment is correlated with both growth averaged over the entire larval phase and larval duration, but not with growth of larvae up to 40 days after hatching (Campana 1996). Our ability to detect correlations involving early growth was likely to be enhanced by rapid otolith growth in A. chirurgus: newly hatched fish have increments ~3 µm wide, and increment width increased to 16 µm at ~20 days.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Rather, early growth per se simply had much more important effects on mortality than later growth, effects that were preserved till settlement and extended into recruitment. This situation contrasts with that in temperate species such as cod, where recruitment is correlated with both growth averaged over the entire larval phase and larval duration, but not with growth of larvae up to 40 days after hatching (Campana 1996). Our ability to detect correlations involving early growth was likely to be enhanced by rapid otolith growth in A. chirurgus: newly hatched fish have increments ~3 µm wide, and increment width increased to 16 µm at ~20 days.…”
Section: Discussioncontrasting
confidence: 45%
“…Our ability to detect correlations involving early growth was likely to be enhanced by rapid otolith growth in A. chirurgus: newly hatched fish have increments ~3 µm wide, and increment width increased to 16 µm at ~20 days. In temperate fishes, increment widths remain at or smaller than the minimum found in A. chirurgus for many weeks after hatching (Campana 1996;Suthers et al 1999). When growth is rapid and increments are wide, variation in rates among individuals can be great and measurement errors are relatively small, allowing statistical tests to readily detect differences among cohorts at young ages (Meekan 1997;Meekan et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…However, such divergence in size could lead to differences in survivorship of larval groups. Campana (1996) estimated the survivorship of cod based on an annual variability in cod mean growth rates of 15%, which is of the same order as the spatial variability in growth rates found in the present study. He used a constant instantaneous mortality rate of 0.1 d -1 , and for larvae having a 15% lower growth rate he estimated a 4-fold increase in cumulative mortality to settlement (at 36 mm) due to the longer larval period.…”
Section: Discussionsupporting
confidence: 59%
“…There is growing evidence from field-based research that enhanced growth rates in the larval stages play an important role in the survival rate of the early life stages of a wide range of species (Hovenkamp, 1992;West and Larkin, 1987;Post and Prankevicius, 1987;Wilson and Meekan, 2002;Rilling and Houde, 1999), showing their influence on recruitment success in a number of species (Campana, 1996;Bergenius et al, 2002). It is reasonable to expect a relationship between larval growth and recruitment because studies on other anchovy species have shown that survival within each ontogenic larval stage is size-specific and growth-dependent (Rilling and Houde, 1999), that mortality declines with age, and that one of its main causes is predation (Leak and Houde, 1987;Folkvord and Hunter, 1986).…”
Section: Discussionmentioning
confidence: 99%